Crecimiento urbano y habitabilidad : un modelo analítico-valorativo para el espacio público urbano - Compagnoni, Ana María (2022)
Over the past decades, forms of urban growth in developing countries have generated increasing problems of fragmentation and urban dispersion, requiring the definition of local parameters adapted to specific environmental conditions, to achieve a balance between the Compact City and the Diffuse City with appropriate urban habitability conditions. In this sense, it is of particular interest to enhance the role of public space as an integrator and moderator of fragmented metropolitan environments. The problem identified for this research is the lack of tools to undertake comprehensive assessments and promote the habitability and quality of life in public spaces affected by urban fragmentation and dispersion. In this framework, the need arises to develop procedures and tools that allow monitoring the built habitat to achieve a better public space performance in its environmental context, as a contribution to sustainable urban growth. \nTherefore, the objective of this thesis is to provide a Valuation Analytical Model of habitability conditions to assess the incidence of design and planning variables of the urban habitat on public space quality and performance. The Municipality of General San Martín is chosen as a study area, a diverse district representative of the conditions typical of the inner sector of urban expansion of the Metropolitan Area of Buenos Aires. The natural conditions of the territory, the environmental and climatic factors of the area are studied, and the historical process of land occupation and its environmental consequences are analyzed. \nBased on a diverse theoretical framework, forms of urban growth are identified as case studies with representative analysis units of the typical public spaces of the area, selected as the base matrix of the research. Three dimensions of public space are defined: morphology, materiality and functionality, and their interaction with the sustainability fields, based on a matrix that allows identifying attributes and variables involved. These attributes form a valuation analytical model of habitability for public urban space, allowing an integrated evaluation of the three dimensions within the framework of urban sustainability in the units selected for each case study. This procedure facilitates both the observation and qualification of habitability achieved in the current conditions of the city while allowing revision and adjustments to optimize the results obtained, as well as to anticipate the future performance of potential urban growth. It is estimated that this tool will provide a useful contribution to the development of planning regulations aimed at promoting forms of urban growth in balance with habitability conditions, contemplating the diversity of incident factors and minimizing the impact of the built habitat on the environment. It also offers a contribution to the understanding of urban habitats and to the interpretation of the aspects that condition its habitability. The work contributes to enhancing the design practice, leading it towards a better balance between the built environment and the open public space, providing a verification and implementation tool, both for the regulatory development and the urban project.